Efficacy and safety of artemether-lumefantrine compared with quinine in pregnant women with uncomplicated Plasmodium falciparum malaria: an open-label, randomised, non-inferiority trial. - Piola, P; Nabasumba, C; Turyakira, E; Dhorda, M; Lindegardh, N; Nyehangane, D; Snounou, G; Ashley, E; Mcgready, R; Nosten, F; Guerin, P (2010)
Malaria in pregnancy is associated with maternal and fetal morbidity and mortality. In 2006, WHO recommended use of artemisinin-based combination treatments during the second or third trimesters, but data on efficacy and safety in Africa were scarce. We aimed to assess whether artemether-lumefantrine was at least as efficacious as oral quinine for the treatment of uncomplicated falciparum malaria during the second and third trimesters of pregnancy in Mbarara, Uganda.